US-China Trade War : Mixed Currency Fortunes? - Kikuchi, Tomoo (2019)
The dilemma of the US is to restore the manufacturing sector and the fiscal balance of the indebted nation at the same time. To solve this dilemma and the shortage of liquidity in global financial markets, the Chinese yuan and the Japanese yen will have to be further internationalised.